Policy and practice of self-reliance guidance in Indonesian correctional institutions: A systematic literature review - Meissy Dwi Ayu; Kusmiyanti Kusmiyanti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of self-reliance development programs in Indonesian correctional institutions using a Systematic Literature Review (SLR) approach. The primary objective is to identify the gap between the regulatory framework and the actual implementation of vocational programs for inmates. The study employs a qualitative design, synthesizing 42 scholarly articles published between 2020 and 2025, selected through PRISMA methodology and accessed via scholarly databases such as Google Scholar, GARUDA, and Publish or Perish. The review focuses on two central issues: the disparity between policies and practices and the factors influencing the low participation of inmates in self-reliance programs. The findings reveal that while the national target for inmate productivity was reported at 71.34%, this figure only represents 3.2% of the total inmate population in Indonesia. Contributing factors include overcrowding, inadequate facilities, lack of qualified personnel, and inconsistent program execution. The study concludes that although self-reliance development is a mandated aspect of correctional rehabilitation, its actual application remains limited and often ineffective. To improve outcomes, the research recommends enhanced infrastructure, strategic partnerships with industry, personalized inmate engagement, and alignment between training content and labor market needs. This study offers actionable insights for policymakers and correctional practitioners to strengthen rehabilitation programs and support the reintegration of inmates into society.